RESPON MACAM VARIETAS PADI MERAH TERHADAP WAKTU PEMBERIAN NANOSILIKA - Aziz Asrovi; Djoko Heru Pamungkas; Yekti Maryani (JURNAL ILMIAH AGROUST, 2026)
This study aimed to determine the interaction between different red rice varieties (Segreng, Sembada, Pamelen) and the application of NPK Phonska fertilizer combined with various nanosilica application timings on the growth and yield of red rice plants. The research was conducted from May to August 2022 at the Agricultural and Rural Training Center (ARTC) “Lestari Makmur” in Bantul, Yogyakarta. The experimental design used was a Completely Randomized Block Design (CRBD) with two factors: rice variety and nanosilica application timing, each consisting of three levels. This resulted in 9 treatment combinations, each replicated three times. The results showed significant interactions between rice variety and nanosilica application timing on several growth and yield variables, including plant height, fresh and dry biomass, number and length of panicles, and percentage of filled grains. The Pamelen variety with NPK Phonska and nanosilica applied at 25, 50, and 75 days after transplanting (DAT) produced the highest yield in terms of panicle number, panicle length, 1000-grain weight, and grain yield per hectare. Meanwhile, the Segreng variety showed the best response in vegetative growth. Gradual nanosilica application proved effective in enhancing nutrient absorption efficiency and improving red rice productivity. This study recommends the combination of the Pamelen variety and nanosilica application at 25, 50, and 75 DAT as the most optimal treatment for increasing red rice yield.